Inhibition of acetylcholine-activated K(+) currents by U73122 is mediated by the inhibition of PIP(2)-channel interaction - Cho, Hana (2001)
1. We have investigated the effect of U73122, a specific inhibitor of phospholipase C (PLC), on acetylcholine-activated K(+) currents (I(KACh)) in mouse atrial myocytes. 2. In perforated patch clamp mode, I(KACh) was activated by 10 μM acetylcholine. When atrial myocytes were pretreated with U73122 or U73343, I(KACh) was inhibited dose-dependently (half-maximal inhibition at 0.12±0.0085 and 0.16±0.0176 μM, respectively). The current-voltage relationships for I(KACh) in the absence and in the presence of U73122 showed that the inhibition occurred uniformly from −120 to +40 mV, indicating a voltage-independent inhibition. 3. When U73122 was applied after I(KACh) reached steady-state, a gradual decrease in I(KACh) was observed. The time course of the current decrease was well fitted to a single exponential, and the rate constant was proportional to the concentration of U73122. 4. When K(ACh) channels were directly activated by adding 1 mM GTPγS to the bath solution in inside-out patches, U73122 (1 μM) decreased the open probability significantly without change in mean open time. When K(ACh) channels were activated independently of G-protein activation by 20 mM Na(+), open probability was also inhibited by U73122. 5. Voltage-activated K(+) currents and inward rectifying K(+) currents were not affected by U73122. 6. These findings show that inhibition by U73122 and U73343 of K(ACh) channels occurs at a level downstream of the action of Gβγ or Na(+) on channel activation. The interference with phosphatidylinositol 4,5-bisphosphate (PIP(2))-channel interaction can be suggested as a most plausible mechanism.